STUDI ELEKTROKIMIA EKSTRAK BETALAIN UMBI BIT SEBAGAI PEWARNA ALAMI DSSC (DYE SENSITIZED SOLAR CELL) - Elma Alfianti Indri Lestari; Pirim Setiarso (Department of Chemistry, Faculty of Mathematics and Natural Sciences, Surabaya State University, located at Jl Ketintang, Surabaya, East Java, Indonesia, 2021)
This research was conducted to explore and utilize fresh beetroot as raw material for natural dyes in DSSC. DSSC (Dye Sensitized Solar Cell) is a photovoltaic cell that can convert sunlight into electricity using environmentally friendly raw materials and low production costs. In this study, DSSC was made using the doctor blade method using natural dyes derived from betalain tuber extract. beet. Natural dyes were chosen because they are easy to obtain, as well as cheap and environmentally friendly. The betalain from the beetroot is macerated with ethanol as a solvent. Characterization of natural dyes was carried out using UV-Visible spectrophotometry to determine the wavelength absorption, electrochemical characterization of dyes was carried out using cyclic voltammetry, and to determine the efficiency of the DSSC was carried out by I – V characterization. In this study, an absorption wavelength of 534 nm was produced which showed the uptake of the pigment betasianin. The electrochemical characterization showed that the energy of the HOMO (Highest Occupied Molecular Orbital) in the dye was -5.00 eV. The LUMO (Lowest Unoccupied Molecular Orbital) energy in dye is -3.71 eV. Analysis of the energy bandgap (energy gap) of the dye yields 1.29 eV, meaning that the prepared dye can be used as a sensitizer on the DSSC. I-V characterization showed that the efficiency value of DSSC with natural dye for beetroot was 0.004%. These results indicate that the natural dye extract of beetroot betalain can be used as a natural dye in DSSC. Key words: betalain,DSSC,electrochemical